2016
DOI: 10.1016/j.tre.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

A strategic analysis of incorporating CSR into managerial incentive design

Abstract: A strategic analysis is conducted to incorporate corporate social responsibility (CSR) considerations into managerial incentive design in a duopoly where each firm comprises an owner and a manager. Consumer surplus is adopted to represent the firms' CSR concerns and a CSR-related incentive is introduced to accommodate both profit and consumer surplus. Bertrand and Cournot competition modes are discussed with the firms' products being complementary, independent, or substitutable. We first examine the equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…The recent topic on CSR has received increasing attention from broad research in both empirical and theoretical analyses in the areas of in business and economics. 5 For example, some theoretical papers including Goering (2012Goering ( , 2014, Kopel and Brand (2012), Grothe (2013, 2015), Nakamura (2014), Chang, et al (2014), Kopel (2015), Lambertini and Tampieri (2015) and Bian, et al (2016) analyzed different models of oligopolies where profit-maximizing private firms compete with other private firms that adopt CSR activities.…”
Section: Introductionmentioning
confidence: 99%
“…The recent topic on CSR has received increasing attention from broad research in both empirical and theoretical analyses in the areas of in business and economics. 5 For example, some theoretical papers including Goering (2012Goering ( , 2014, Kopel and Brand (2012), Grothe (2013, 2015), Nakamura (2014), Chang, et al (2014), Kopel (2015), Lambertini and Tampieri (2015) and Bian, et al (2016) analyzed different models of oligopolies where profit-maximizing private firms compete with other private firms that adopt CSR activities.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning CSR-related incentives,Kopel and Brand (2012),Brand and Grothe (2015) andBian, et al (2016) also considered the managerial incentive design and showed that the emergence of a CSR firm can enhance its profitability, compared to pure profit-seeking firms.4 The importance of the eco-industry has been recognized by policy reports in international institutions. According to Environmental Business International (2012), the global market size of the eco-industry was approximately US$838 billion in 2010 and is expected to reach US$992 billion by 2017.…”
mentioning
confidence: 99%
“…In keeping with previous publications [1,2,5,6,9,11,17,24], a socially responsible firm's CSR in our model setting is accounted for in the form of a share of consumer surplus. The CSR firm's objective is to maximize her (or his) traditional pure profit plus a portion of consumer surplus accumulated from stakeholders.…”
Section: Model Developmentmentioning
confidence: 81%
“…It is well known that Toyota applies the learning curve to its production system which focuses on the continuous improvement of processes [25]. CNBC said that Sony and Microsoft will ultimately benefit as the cost to produce their consoles decreases according to the normal learning curve dynamics in the electronics industry 1 . Cost learning effects have been studied widely in traditional supply chains [7,10,29].…”
Section: Introductionmentioning
confidence: 99%